Android Apps with Eclipse - Cinar, Onur (Apress : Imprint: Apress, 2012)
Eclipse is the most adopted integrated development environment (IDE) for Java programmers. And, now, Eclipse seems to be the preferred IDE for Android apps developers. Android Apps with Eclipse provides a detailed overview of Eclipse, including steps and the screenshots to help Android developers to quickly get up to speed on Eclipse and to streamline their day-to-day software development. This book includes the following: Overview of Eclipse fundamentals for both Java and C/C++ Development. Using Eclipse Android Development Toolkit (ADT) to develop, debug, and troubleshoot Android applications. Using Eclipse C/C++ Development Toolkit (CDT) in conjunction with Android Native Development Kit (NDK) to integrate, develop and troubleshoot native Android components through Eclipse.